THE USE OF Cymbopogon nardus AS Aedes aegypti LARVASIDA - S.D., Endah Rita; Ningtyas, Dewi Ratna (BIOMA, 2011)
ABSTRACT Control of mosquitoes as vectors of disease is generally performed using synthetic pesticides, with all its negative impacts. So it takes an effort to obtain alternative materials which are more environmentally friendly but also effective in controlling insects that is botanical pesticides. This study aims at: 1) determining the correct dosage of  leaves extracts and stem of citronella as a botanical pesticide exterminator of  Aedes aegypti mosquito larvae;  2) determining LD50 extracts of leaves and stems of citronella and safe limits for non target organisms. This research was done in Salatiga B2P2VRP Laboratory and the Laboratory of Organic Chemistry, Department of Chemistry, Faculty of Science, University of Diponegoro. The method used is a bioassay (biological assay) , i.e. acute toxicity testing of chemicals using the or-ganism as a test animal. Subjects were Aedes aegypti three sub stadium (instar) as test target animals, and Goldfish (Carassius auratus) as test animals are not the target. Data obtained from test animals actually target and non target animals were analyzed and interpreted by a simple linear regression analysis. The result showed  that  LD100 Aedes aegypti larvae mortality was  24575 ppm, and the LD50 is amounted to 35000 ppm, then the safe limit for other non target organism (environment) is 3500 ppm. The conclusion is that citronella (Cymbopogon nardus) can be used as a botanical pesticide with a safe margin for other organisms is 3500 ppm. Key words: Cymbopogon nardus, larvasida, Aedes aegypti, LD50, Carassius auratus.